2020
DOI: 10.1098/rsta.2020.0266
|View full text |Cite
|
Sign up to set email alerts
|

The changing Arctic Ocean: consequences for biological communities, biogeochemical processes and ecosystem functioning

Abstract: One contribution of 18 to a theme issue 'The changing Arctic Ocean: consequences for biological communities, biogeochemical processes and ecosystem functioning'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The vertical distribution of Chl-a (st. 4) displayed a notable increase at the 25 and 50 m depth, with values five times higher than the surface, indicating a typical condition of the stratified water column. Total Chl-a concentrations measured in this study were comparable to those reported by Iversen and Seuthe [28] (0.18 ± 0.01 µg/L), who also found POC concentrations of 314 ± 46 µg/L in May and minimum ratios (4.6) of C:N. Wide variations in primary productivity are currently recorded in Kongsfjorden, due to pronounced seasonal variations in sunlight, glacier melting, and sea ice cover; all these conditions largely affect the downward export of biogenic matter [69]. Melted ice water inputs from several tidewater glaciers (Kongsbreen, Conwaybreen, Blomstrandbreen, Kronebreen, and Kongsvegen) enrich the fjord with particles of mineral and organic origin [31,32,70,71].…”
Section: Environmental Characterizationsupporting
confidence: 90%
See 2 more Smart Citations
“…The vertical distribution of Chl-a (st. 4) displayed a notable increase at the 25 and 50 m depth, with values five times higher than the surface, indicating a typical condition of the stratified water column. Total Chl-a concentrations measured in this study were comparable to those reported by Iversen and Seuthe [28] (0.18 ± 0.01 µg/L), who also found POC concentrations of 314 ± 46 µg/L in May and minimum ratios (4.6) of C:N. Wide variations in primary productivity are currently recorded in Kongsfjorden, due to pronounced seasonal variations in sunlight, glacier melting, and sea ice cover; all these conditions largely affect the downward export of biogenic matter [69]. Melted ice water inputs from several tidewater glaciers (Kongsbreen, Conwaybreen, Blomstrandbreen, Kronebreen, and Kongsvegen) enrich the fjord with particles of mineral and organic origin [31,32,70,71].…”
Section: Environmental Characterizationsupporting
confidence: 90%
“…The intrusion of warm waters of Atlantic origin is particularly enhanced during late summer, while during fall and winter, the fjord water masses are replaced by fresher and cold Arctic waters [21]. In addition to the WSC inputs, in summer, the freshwater runoff from land and glaciers produces strong gradients inside the fjord, which also led to stratification at shallow depths [28]. Inter-annual variability in the water masses and Atlantic water intrusion, with a net outflow of surface freshwater from Kongsfjorden, has, however, recently been documented [35].…”
Section: Study Area and Collection Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arctic Ocean is experiencing ongoing changes associated with receding sea ice, warming, and acidification that have large consequences for biological productivity and higher marine life (Solan et al, 2020;Stroeve & Notz, 2018;Terhaar et al, 2020). Elevated water temperatures have resulted in loss of summer sea ice, increased light transmission, a prolonged growing…”
Section: Introductionmentioning
confidence: 99%
“…
The Arctic Ocean is experiencing ongoing changes associated with receding sea ice, warming, and acidification that have large consequences for biological productivity and higher marine life (Solan et al, 2020;Stroeve & Notz, 2018;Terhaar et al, 2020). Elevated water temperatures have resulted in loss of summer sea ice, increased light transmission, a prolonged growing season (Serreze et al, 2007), and an increase in primary production by 30% over the period of 1998-2012, especially on the inner eastern Siberian shelf (Arrigo & Van Dijken, 2015).The Arctic shelf is the largest continental shelf on Earth and makes up >50% of the total Arctic Ocean area (Jakobsson, 2002).
…”
mentioning
confidence: 99%